REFLEKSI METAFISIK PADA SIMBOL MAJANG DAN TARUB DALAM UPACARA PERKAWINAN ADAT JAWA (GAYA JOGJAKARTA) - Rochani, Dewi (Jurnal Filsafat "WISDOM", 2009)
AbstractJavanese always makes symbols that reflect their philosophyof life. One of them is in their wedding ceremony, especiallyâ€œMajangâ€ and â€œTarubâ€. The â€œMajangâ€ and â€œTarubâ€, which is such wedding materials, symbolize expectations of Javanese familyto bride and groom in order to get happiness and peaceful life, and messages/ advices to the audience. The Javanese have insights that the quantity of reality tends to be monism. The quality of reality tends to be spiritualism but it still gives us a room to think rationally and pragmatically. The dynamic of reality tends to be idealism without ignoring the realism of life. The ontology norm of Javanese shows a harmony with surroundings, natural and supernatural life.Keyword: majang, tarub, monism, spiritualism, idealism, fatalism, harmony, ritual.